Analysis of Students' Learning Needs for Teaching Materials in Informatics Subject at Senior High School.: Analisis Kebutuhan Belajar siswa Pada Mata Pelajaran Informatika di Sekolah Menengah Atas - Fitri, Rahmi Yuliza; Alfiriani, Adlia; Siska, Felia (Pedagogia : Jurnal Pendidikan, 2025)
Education in the digital era requires innovative learning, especially in informatics, which develops critical thinking, problem-solving, and digital literacy. However, many schools, including SMA Negeri 2 Pasaman, struggle to provide relevant teaching materials. This study analyzes students' learning needs through a quantitative survey of 98 tenth-grade students. Results show that lectures (31%) and printed books (80%) dominate learning, while students prefer interactive materials with clear content, exercises, images, videos, and animations. The findings highlight the gap between available materials and students’ needs, emphasizing the need for more innovative, engaging, and relevant teaching resources. Highlights: Learning Material Gap – Most schools rely on printed books (80%) and lectures (31%), while students prefer interactive materials. Need for Interactive Learning – Students want comprehensive, easy-to-understand materials with exercises, images, videos, and animations. E-Module Solution – Developing interactive digital materials can enhance student engagement and understanding in informatics. Keywords: Needs Analysis, Teaching Materials, Informatics